Analisis Strategi Keamanan Energi Cina dalam Upaya Penurunan Emisi Karbon melalui Pendekatan Konstruktivisme - Chotimah, Hidayat Chusnul (UI Scholars Hub, 2017)
The Chinese government has finally committed itself to reducing carbon emissions after having for years refused to limit its energy consumption levels due to industrialising efforts and economic development needs. The primary reason behind the policy change is the severe, life-threatening environmental damage resulted from industrialisation processes. The Chinese government has now set out strategic measures to safeguard its energy security by harmonising its climate change and economic policies. This is done to achieve carbon emission reduction through energy conservation and green economy development by developing renewable energy such as nuclear energy, hydropower, wind power, solar power and other undiscovered alternative energy sources. The actions taken by the Chinese government are based on existing international norm, namely those stipulated by the climate change regime which in turn formulate China's identity as a responsible country in the collective efforts to reduce carbon emissions. Operating on the basis of climate change norms, China interacts with other actors within the international structure to gather variegated knowledge on the issues at hand. With this accumulated knowledge as guidance, China enacts strategic-instrumental and resources-instrumental deliberations in its commitment to reduce carbon emissions.